Flirting lessons [large type] - Guillory, Jasmine (Center Point Large Print, 2025)
"Avery Jensen is almost thirty, fresh off a breakup, and she's tired of always being so uptight and well-behaved. She wants to get a hobby, date around (especially women), flirt with everyone she sees, wear something not from the business casual section of her closet--all the fun stuff normal people do in their twenties. One problem: Avery doesn't know where to start. She doesn't have a lot of dating experience, with men or women, and despite being self-assured at work, she doesn't have a lot of confidence when it comes to romance. Enter Taylor Cameron, Napa Valley's biggest flirt and champion heartbreaker. Taylor just broke up with her most recent girlfriend, and her best friend bet her that she can't make it until Labor Day without sleeping with someone. So, she offers to give Avery flirting lessons. It should keep her busy and stop her from texting people she shouldn't. And it might take her mind off how inadequate she feels compared to her friends, who all seem much more settled and adult than Taylor. At first, Avery is stiff and nervous, but Taylor is patient and encouraging, and soon, Avery looks forward to their weekly lessons. With Taylor's help, Avery finally has the life she always wanted. The only issue is: now she wants Taylor. Their attraction becomes impossible to ignore, despite them both insisting to themselves and everyone else that it isn't serious. When Taylor is forced to confront her feelings for Avery, she doesn't know what to do and most importantly, she wonders if she's already ruined the best thing she's ever had."--